The Importance of Artificial Intelligence in Nursing: A Fundamentals of Care Perspective - João Oliveira; Paulo Nogueira; Cristina Baixinho; Andreia Costa (Journal of Advanced Nursing, 2026)
ABSTRACT Aim To analyze the integration of Artificial Intelligence in nursing through the lens of the Fundamentals of Care framework. Design A discursive paper. Methods This discursive paper synthesizes current literature and theoretical perspectives to examine the Relationship, Integration and Context dimensions of the Fundamentals of Care framework in the era of Artificial Intelligence. Results Artificial Intelligence offers substantial benefits in optimizing workflow (Context) and clinical precision (Integration) through predictive analytics and automated documentation. However, these technologies cannot replace the psychosocial and relational core of nursing. When used to reduce administrative burden, Artificial Intelligence can theoretically release time for nurses to deepen the therapeutic bond. Conclusion Artificial Intelligence should be viewed not as a competitor but as an enabler for providing person‐centred fundamental care. To ensure ethical integration, nurse leaders must cultivate Artificial Intelligence literacy and maintain the nurse–patient relationship as the central mediator of care. Implications for the Profession and/or Patient Care Nurses must actively participate in the Artificial Intelligence lifecycle to prevent ‘infocratic care’ and ensure algorithms support rather than supplant human connection. Reporting Method None. Patient or Public Contribution None. However, the discussion of this topic is important to ensure quality and safe care for citizens.